Pengembangan Media Pembelajaran Kotak Komponen Ekosistem (KOKOSIS) untuk Sekolah Dasar - Mahardika, Candra; Siswoyo, Andika Adinanda (Pusat Pengembangan Pendidikan dan Bakat Indonesia, 2021)
The objectives of this research are (1) to find out the development of KOKOSIS learning media (Ecosystem Component Box) on the theme 8 sub-theme 1 grade V at UPTD SDN Panyaksagan Klampis; (2) to know the validity, effectiveness, and attractiveness of KOKOSIS learning media (Ecosystem Component Box) at the theme 8 sub-theme 1 grade V at UPTD SDN Panyaksagan Klampis. This development research uses the Borg and Gall development model. Based on the results of the research conducted, the results showed that the average percentage of KOKOSIS learning media’s validity was 89%, hence it can be categorized as very valid. The effectiveness of the KOKOSIS learning media which is being measured from the teacher observations is 100%, hence can be categorized as very active. Meanwhile, the result of the observation on the students’ activity is 98% and can also be categorized as very active. The percentage of classical completeness is 91%, hence it can be categorized as completed. In conclusion, the KOKOSIS learning media can be effectively used in learning process. Furthermore, the media’s attractiveness which is measured by the percentage of student questionnaire response shows that 97% of the students claimed it as attractive, thus it can be categorized as very interesting. Thus, it can be concluded that the KOKOSIS learning media is valid, effective and interesting to be applied in the Theme 8 Sub-theme 1 of ecosystem components topic for V grader at UPTD SDN Panyaksagan Klampis.